Extraction and characterization of humic acids from peat water and coal - Amira Satiraway, Mohamed Pauzan. (Universiti Malaysia Sarawak (UNIMAS), 2004)
Humic acid is a fraction of humic substances which is soluble in base and precipates at pH less than 2. Humic acid is very useful in agriculture. This study determines the optimum condition in extracting high yield of humic acid from peat water and coal. Factors considered in the study were pH and coagulant concentration for peat water and drying method, heat and coal origin for coal. Findings of the study indicated that combination of pH 4.5-5.0 and alum concentration of 50 ppm is the optimum condition for extracting humic acid from peat water while coal fran Kapit showed the highest yield of humic acid extracted through combination of freeze-dried method and addition of heat. The obtained FTIR spectra for peat water humic acid and coal humic acid showed similar pattern to the humic acids obtained from the treatment plant in Asajaya and differences only observed at several ranges.